ADMINISTRATIVE AND LEGAL REGULATION OF STATUS OF A MEMBER OF THE HIGH COUNCIL OF JUSTICE - Голобутовський, Роман Зіновійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the article reveals the issues of administrative-legal regulation of the status of a member of the High Council for Justice. Methods of research: by means of scientific analysis of legislation and work of scientists, the peculiarities of administrative and legal regulation of the status of a member of the Supreme Council of Justice are highlighted. Results: the current state and problems of regulation of the administrative and administrative status of a member of the High Council for Justice are determined. Discussion: the need for changes in legislation on the topic under study. On the basis of the above, it should be noted that the entry into force of the Law of Ukraine «On the High Council of Justice» is a positive step in the implementation of reforms in the judicial system and legal proceedings. Today, an independent body has been formed and functioning in Ukraine, the foun dation for the formation of the judiciary corps and disciplinary liability of judges. At the same time, in order to form a highly professional membership of the High Council for Justice, the following measures aimed at improving the legislation regulating the procedures for the election of members of the High Council of Justice should be taken: all procedures for the nomination and election of members of the High Council for Justice should be regulated by law; it is necessary to specify and increase the requirements for the professional qualities of a member of the High Council of Justice; the requirements for the impartiality of a member of the High Council of Justice should be increased and conflicts of interest should be avoided when fulfilling their obligations.